Smoking reduces cathelicidin LL-37 and human neutrophil peptide 1–3 levels in the gingival crevicular fluid of patients with periodontitis - Soldati, Kahena R. [UNESP]; Toledo, Felipe A. [UNESP]; Aquino, Sabrina G.; Rossa, Carlos [UNESP]; Deng, Dongmei; Zandim-Barcelos, Daniela L. [UNESP] (Wiley, 2020)
Background: Antimicrobial peptides are components of innate immune response that have a key role on susceptibility and resistance of the oral cavity to diseases. This study aimed to investigate the influence of smoking on cathelicidin LL-37 and human neutrophil peptides 1 through 3 (HNP 1‒3) levels in the gingival crevicular fluid (GCF) of patients with periodontitis. The relationship between levels of these peptides with the periodontal status and selected inflammatory mediators levels in smokers and non-smokers was also evaluated. Methods: Forty patients with periodontitis, 20 smokers and 20 non-smokers were recruited. After a full periodontal clinical assessment, GCF samples were collected from healthy (n = 5) and diseased (n = 5) sites of each patient. Peptides and inflammatory mediators in the GCF were quantitated by sandwich ELISAs and Multiplex assay, respectively. Results: Diseased sites had significantly (P <0.05) higher levels of LL-37 and lower levels of HNP 1‒3 than healthy sites in both smokers and non-smokers. Diseased sites of smokers presented significantly lower levels of LL-37 and HNP 1‒3 when compared with diseased sites of non-smokers. Concentration of LL-37 was directly correlated with the presence of proinflammatory mediators matrix metalloproteinase (MMP)-8 and interleukin (IL)-1β and inversely correlated with concentration of IL-10. HNP 1‒3 concentration was positively correlated with IL-10 and negatively correlated with concentrations of MMP-8 and IL-1β. Conclusions: Smoking was associated with reduced levels of LL-37 and HNP 1‒3 in GCF of patients with periodontitis. LL-37 had a distinct expression pattern from HNP 1‒3: LL-37 was upregulated in diseased sites, and HNP 1‒3 was increased in periodontally healthy sites.1.
Keywords: alpha-defensins; cathelicidins; cationic antimicrobial peptides; inflammation mediators; periodontitis; smoking